Implementation of a provincial acute stroke pathway and its impact on access to advanced stroke care in Saskatchewan - Michael E Kelly; Lissa Peeling; Jessica Hamilton; Laura Schwartz; Jessalyn K Holodinsky; Vivian N Onaemo; Ruth Whelan; Gary Hunter; Brett R Graham; Lori Latta (BMJ Open Quality)
Background For ischaemic stroke, outcome severity is heavily time dependent. Systems of care need to be in place to ensure that patients with stroke are treated quickly and appropriately across entire health regions. Prior to this study, the province of Saskatchewan, Canada did not have a provincial stroke strategy in place.Methods A quality improvement project was undertaken to create and evaluate a provincial stroke strategy. The Saskatchewan Acute Stroke Pathway was created using a multidisciplinary team of experts, piloted at five stroke centres and then implemented provincially. The number of stroke alerts, door-to-imaging, door-to-needle, door-to-groin puncture times and treatment rates were collected at all centres. Improvements over time were analysed using run charts and individuals control charts.Results The number of stroke alerts province-wide trended upwards in the last 6 months of the study. There were no clear trends or shifts in the proportion of stroke alerts treated with alteplase or endovascular therapy. Across the province, the weighted mean door-to-imaging time decreased from 21 to 15 min, the weighted mean door-to-needle time decreased from 62 to 47 min and the mean door-to-groin puncture time decreased from 83 to 70 min. There was high variability in the degree of improvement from centre to centre.Conclusions The implementation of a province wide acute stroke pathway has led to improvement in stroke care on a provincial basis. Further work addressing intercentre variability is ongoing.